Pengaruh Akuntabilitas dan Transparansi Pengelolaan Zakat Terhadap Minat Muzaki Membayar Zakat Pada Era Pandemi Covid-19 - Halijah, Nur (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
This study aims to determine whether or not there is an influence of accounability and transparency of zakat management on the interest of muzaki to pay zakat in the area of the covid-19 pandemic at the National Amil Zakat Agencyof Asahan Regency. The independent variables used in this study are accountability and transparency. While the dependent variable is the interest of muzaki. The source of data in this study is primary data with the data collections method using a questionnaire distributed in the scope of BAZNAS, Asahan Regency. The number of samples whose data was succesfully processed was 91 people. The sampling technique used is non-probability sampling with convinience sampling method. The results of hypotesis testing for the accountability variable in the study are indicated by the value of the tcount (3,540) > ttable (1,987) and for the transparency variable it is indicated by the value of tcount (5,144) > ttable (1,987). While the results of the F test for the accountability and transparency variables are simultaneously shown by the value of fcount (85,251) > ftable (3,099). So, the results of the t-test and F-test show that accountability and transparency have a partial and simultaneous effect on the interest of muzaki to pay zakat during the covid-19 pandemic era at the National Amil Zakat Agency Of Asahan Regency.